Trial Braille Audio Media Development for Disability Foreign Student and Its Validation - Widiyono, Yuli; Setyowati, Herlina; Aryanto, Aris; Rochimansyah, Rochimansyah; Chen, Chuang; Fogly , Luana (Scripta : English Department Journal, 2024)
Individuals with disabilities have equal rights to access education. For Disabilities Foreign Student (DFS), it is important to assist them in learning javanese scripts in Javanese Language and Literature Education Program (PBSJ). The development of a Braille audio media application (BAM) for script-based learning using technology was explored. This study aimed to analyze the validity of developing Braille audio media. The development method employed a 4-stage model: Define, Design, Develop, and Disseminate, adapted into a 4-D model. The Javanese script Braille audio media application was developed using the Software Development Life Cycle (SDLC) Waterfall model, encompassing planning, modeling, implementation, and testing phases. Validation results from practitioners and academics indicated that the media aspect validation was 82.5%, and validation from subject matter experts was 78.75%, both categorized as suitable. Developing the BAM based on information technology aids foreign students with disabilities in learning and exploring Javanese cultural values through Javanese scripts.